2009
DOI: 10.1089/apc.2008.0222
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Beliefs, and Health Care Practices Relating to Treatment of HIV in Vellore, India

Abstract: In India, little is known about health care-seeking behavior among HIV-infected individuals. Similarly, little is known about how HIV is being treated in the community, in particular by Indian Systems of Medicine (ISM) providers. Therefore, while ART implementation programs continue to expand, it is important to determine whether the knowledge, attitudes, and treatment practices of HIV-infected individuals and their health care providers are aligned with current treatment recommendations. We conducted in-depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
23
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 39 publications
(66 reference statements)
2
23
0
Order By: Relevance
“…The finding however supports previous studies from Africa, South America and Asia where misconceptions about drugs or other care were vital for health seeking behavior [22,23,29,[55][56][57]. The concept of negative perceptions and dangerous misconceptions affecting HIV diagnosis and ARV treatment has similarly been established by other studies in resource-poor settings [23,36,[58][59][60].…”
Section: Discussionsupporting
confidence: 87%
“…The finding however supports previous studies from Africa, South America and Asia where misconceptions about drugs or other care were vital for health seeking behavior [22,23,29,[55][56][57]. The concept of negative perceptions and dangerous misconceptions affecting HIV diagnosis and ARV treatment has similarly been established by other studies in resource-poor settings [23,36,[58][59][60].…”
Section: Discussionsupporting
confidence: 87%
“…The dominance of private health care is partly attributed to its reputation as more efficient, convenient and confidential than public sector services (Bhat, 1999; Sheikh, Porter, Kielmann, & Rangan, 2006). However, the medical mismanagement respondents faced whereby they were treated for many other conditions before HIV was diagnosed echoes previous research where private practitioners were frequently found not following current HIV guidelines (Chomat et al, 2009; Datye et al, 2006; Kielmann et al, 2005). …”
Section: Discussionmentioning
confidence: 74%
“…This specifically translated into three times higher likelihood of being infected with HIV-1 if presenting for care late in the (Cohen et al, 2008;Kupka et al, 2009;Lemos et al, 2009;Pai et al, 2008). It is unknown, if this phenomenon is due to a prior knowledge of HIV status and stigma and discrimination related to that , versus a general lack of health seeking behavior among HIV-positive women (Chomat et al, 2009). We think it is the latter, as a higher percentage of HIV-positive women were primigravida, with little probability of having HIV testing outside of antenatal care.…”
Section: Discussionmentioning
confidence: 99%
“…Rogers et al, 2006;Samuel et al, 2007;Shrotri et al, 2003;Sinha et al, 2008;Solomon et al, 2003). It has been shown that their main sources of information on AIDS are health workers and television (Chatterjee, 1999a;Chomat et al, 2009;Kunte et al, 1999), both of which are amenable to targeted interventions and uptake regardless of the educational level of the women. Since marriage and motherhood are important in the Indian cultural context, male spouses should be included in riskreduction programs (M.C.…”
Section: Discussionmentioning
confidence: 99%